2019
DOI: 10.1172/jci130630
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin administration into the subarachnoid space prevents hemoglobin-induced cerebral vasospasm

Abstract: Statistics. We used JMP software from SAS (versions 13 or 14) for all analyses. Data are presented with all data points plotted. Overlayed diamonds represent mean, 95% CI, and overlap marks (horizontal lines above and below the mean line), which define statistical significant difference between groups if not overlapping (P < 0.05). Groups were compared with 1-way ANOVA, applying a Tukey-Kramer posttest correcting for multiple comparisons. A P value of less than 0.05 was considered statistically significant.Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 104 publications
4
100
0
Order By: Relevance
“…It has been recently demonstrated that secondary vasospasm (due to NO inhibition by Hb) and neurotoxicity (due to subarachnoid hemorrhage) were rescued by the infusion of Hp in the cerebral spinal fluid, by a direct inhibition and sequestration of Hb-Hp complexes (m.w. > 100 kD) [104]. With regard to intact RBCs, erythrophagocytosis by microglia [105] is usually insufficient to prevent free hemoglobin release and neurotoxicity.…”
Section: Strokementioning
confidence: 99%
“…It has been recently demonstrated that secondary vasospasm (due to NO inhibition by Hb) and neurotoxicity (due to subarachnoid hemorrhage) were rescued by the infusion of Hp in the cerebral spinal fluid, by a direct inhibition and sequestration of Hb-Hp complexes (m.w. > 100 kD) [104]. With regard to intact RBCs, erythrophagocytosis by microglia [105] is usually insufficient to prevent free hemoglobin release and neurotoxicity.…”
Section: Strokementioning
confidence: 99%
“…Recently, it was shown that cell-free Hb from cerebrospinal fluid in vascular structures is the primary cause of aneurysmal subarachnoid hemorrhage pathophysiology [116]. Indeed, RBC destruction in the subarachnoid space leads to an accumulation of cell-free Hb, exceeding haptoglobin scavenger capacity in the cerebrospinal fluid.…”
Section: Harmful Effects Of Heme On Endotheliummentioning
confidence: 99%
“…Indeed, RBC destruction in the subarachnoid space leads to an accumulation of cell-free Hb, exceeding haptoglobin scavenger capacity in the cerebrospinal fluid. This unbound Hb thus promotes spasms in cerebral arteries and smaller parenchymal arterioles [116]. In a sheep model, administration of Hp into the cerebrospinal fluid inhibited Hb-induced cerebral vasospasm and preserved vascular NO-signaling.…”
Section: Harmful Effects Of Heme On Endotheliummentioning
confidence: 99%
“…If they did, the would immediately attack the haem ring or the adjacent amino acid residues and would be unlikely to be released into free solution [ 8 ]. Nevertheless, it is indeed the case that haem and, in the presence of H 2 O 2 , haem proteins such as myoglobin, haemoglobin and cytochrome c can be powerful pro-oxidants, a process that is important in vivo , the kidney and brain being especially sensitive targets of oxidative damage by haem proteins [ 129 , 130 ]. There are two aspects to these pro-oxidant effects ( Fig.…”
Section: Ironic Burgersmentioning
confidence: 99%